Analysis of Sharia Hotel Standardization According to the Indonesian Council of Ulama (MUI) Fatwa at Arabia Style Hotel - Azura Rizti Saladin; Zuhrinal M Nawawi; Purnama Ramadani Silalahi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study aims to analyze the standardization of sharia hotels based on the Indonesian Ulema Council (MUI) Fatwa No. 108/DSN-MUI/X/2016 using the Balanced Scorecard approach, focusing on Hotel Arabia Style in Medan. The Balanced Scorecard was employed to evaluate the hotel’s performance from four perspectives: internal business processes, learning and growth, customer, and financial. Data were collected through questionnaires distributed to 13 employees and 20 guests of the hotel. The findings reveal that: (1) From the internal business process perspective, the hotel has implemented several sharia principles but lacks sufficient sharia supervision and still utilizes conventional banking services; (2) The learning and growth perspective shows that while the hotel has policies ensuring staff adhere to Islamic dress codes, it has yet to establish a Sharia Supervisory Board within its organizational structure, with employee satisfaction reaching 89.6%; (3) The customer perspective indicates a high customer satisfaction rate of 90%, demonstrating that the hotel successfully meets customer expectations, particularly in providing services in line with Islamic values; and (4) The financial perspective shows positive results across various measured aspects. This study recommends enhancing sharia supervision and restructuring the financial operations to better align with sharia principles